Mitigation of Paeoniae Radix Alba extracts on H2O2-induced oxidative damage in HepG2 cells and hyperglycemia in zebrafish, and identification of phytochemical constituents - Zhang, Lu; Deng, Mei; Wang, Si-yu; Ding, Qiao; Liu, Jia-hui; Xie, Xing; Huang, Yun-hong; Tu, Zong-cai (Frontiers in Nutrition, 2023)
Paeoniae Radix Alba (PRA), as a Traditional Chinese Medicine, is widely used in Chinese cuisine due to high health-benefits and nutrition, but the effect of different polarity of solvents on the extraction of antioxidant and hypoglycemic constituents, as well as the major active compounds remain unclear. In this research, 40%, 70%, and 95% ethanol were firstly applied to extract the polyphenols from PRA, the extraction yields, total phenolics and total flavonoids content, free radical scavenging ability, α-glucosidase inhibition ability and anti-glycation ability of extracts were evaluated spectroscopically. The oxidative damage protection, hypoglycemic activity and alleviation on peripheral nerve damage were evaluated by H2O2-induced HepG2 cells and hyperglycemic zebrafish models. UPLC-QTOF-MS/MS was used to identify the major chemical constituents. The results showed that 40%, 70%, and 95% ethanol exhibited insignificant difference on the extraction of phenolics and flavonoids from PRA. All extracts showed promising DPPH· and ABTS·+ scavenging ability, α-glucosidase inhibition and anti-glycation ability. In addition, PRA extracts could restore the survival rate of HepG2 cells induced by H2O2, and alleviate the oxidative stress by reducing the content of MDA and increasing the levels of SOD, CAT and GSH-Px. The 70% ethanol extract could also mitigate the blood glucose level and peripheral motor nerve damage of hyperglycemic zebrafish. Thirty-five compounds were identified from 70% ethanol extract, gallotannins, gallic acid and its derivatives, paeoniflorin and its derivatives were the dominant bioactive compounds. Above results could provide important information for the value-added application of PRA in functional food and medicinal industry.